Not Ready for College, but Ready for the Military: A Policy Challenge for the College- and Career-Readiness Agenda - Castro, Erin L (Education Policy Analysis Archives, 2015)
This essay examines the Armed Forces Recruiter Access to Students and Student Recruiting Information (Section 9528) provision of the No Child Left Behind Act and its influence on the success of intervention programming for college and career readiness in Title I high schools. Using critical policy analysis, I show how Federal and State policies potentially unfold in local contexts and influence students’ ability and desire to participate in intervention programming aimed at increasing readiness for college and career. I ask whether readiness for college and career includes readiness for the military and argue that readiness intervention programming designed to provide students labeled as not college ready a pathway to postsecondary education may fail if they do not address the permanent legal presence of military recruiters inside underserved schools.